2021
DOI: 10.1101/2021.10.28.21264912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Diabetic ketoacidosis among Patients Living with Type 1 Diabetes in Makkah Al-Mukarramah City

Abstract: ObjectiveTo assess magnitude of diabetic ketoacidosis (DKA) among type-1 diabetics and to identify associated risk factors.MethodsA cross-sectional study was conducted among 236 type-1 diabetics in Makkah Al-Mukarramah City, Saudi Arabia.ResultsAmong participants, 59.3% were males, 44.1% were diabetic for more than 5 years, while 70.8% reported past history of DKA. The main causes of DKA were “first presentation of the disease” (40.9%), and “discontinued treatment” (37%). The HbA1c among 53.6% was above 9%. Al… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…as reflected by high HbA1c levels and increased prevalence of DKA among children and adolescents with T1DM. [9][10][11] Children and adolescents with T1DM need to follow a structured self-management plan that incorporates appropriate insulin use, blood glucose monitoring, adequate physical activity and a healthy balanced diet to ensure good glycaemic control and prevent diabetesrelated complications. 2 However, self-management activities remain suboptimal among this group of patients in many countries, including Saudi Arabia and Malaysia.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…as reflected by high HbA1c levels and increased prevalence of DKA among children and adolescents with T1DM. [9][10][11] Children and adolescents with T1DM need to follow a structured self-management plan that incorporates appropriate insulin use, blood glucose monitoring, adequate physical activity and a healthy balanced diet to ensure good glycaemic control and prevent diabetesrelated complications. 2 However, self-management activities remain suboptimal among this group of patients in many countries, including Saudi Arabia and Malaysia.…”
Section: Open Accessmentioning
confidence: 99%
“… 8 In addition, several studies from Saudi Arabia reported highlighted poor glycaemic control as reflected by high HbA1c levels and increased prevalence of DKA among children and adolescents with T1DM. 9–11 …”
Section: Introductionmentioning
confidence: 99%